Zoonotic malaria requires new policy approaches to malaria elimination - Fornace, Kimberly M.; Drakeley, Chris J.; Lindblade, Kim A.; Jelip, Jenarun; Ahmed, Kamruddin (Nature communications, 2023)
Increasing numbers of human zoonotic malaria cases are reported globally. Current malaria control measures cannot eliminate transmission from wildlife reservoirs, leaving many countries with no pathway to malaria elimination certification. New policies are needed to redefine elimination goals and certification. WHO guidelines for classification of malaria elimination in a country require that the risk of human infection from zoonotic, as well as nonzoonotic, malaria parasites is negligible. In this Comment, the authors discuss the implications of this policy for countries, such as Malaysia, with no recent reported nonzoonotic cases but ongoing zoonotic transmission.